Maturational arrest from CD4+8+ to CD4+8- thymocytes in a mutant strain (LEC) of rat (The Rockefeller University Press, 1990)
A mutant strain (LEC) of rats was found to have a novel defect in T cell maturation, that is, arrest of differentiation from CD4+8+ to CD4+8- but not to CD4-8+ thymocytes. FACS analyses demonstrated a deficiency in the CD4+8- T cell subset in the thymus and a marked decrease in CD4+ T cells in peripheral lymphoid organs. Expression of the T cell receptor (TCR)/CD3 complex in CD4+8+ and CD4-8+ thymocytes of LEC rats was normal. Expression of class II major histocompatibility complex (MHC) in the thymus of LEC rats was also the same as that of normal rats. These results indicate that maturational arrest occurs only in the transition pathway from CD4+8+ to CD4+8- thymocytes, and that this mutation can not be attributed to the default of expression of either TCR/CD3, CD4, or class II MHC antigen. Consequently, dysfunction of helper T cells was observed in LEC rats, while killer T cells and B cells functioned normally. Although the complete identification of the origin of this mutation requires further studies, it is hoped that such investigations will throw light on the mechanism of positive selection.